Detection of rail faults using morphological feature extraction based image processing - Taştimur, Canan; Akin, Erhan; Karaköse, Mehmet; Aydin, Ilhan (Institute of Electrical and Electronics Engineers Inc., 2015)
Determining the rail's breakdown has a big importance in railway access. The breakdowns of rails bring about problems such as insecurity, delay of access, and expenditure. In this work, in order to determine the breakdowns of rails using Morphological feature extraction based image processing algorithm is offered. The rail is determined through applying the image processing methods and Hough transform to the received images of rail. Headcheck breakage, apletilik and undulation of defects are determined by proposed method. Faulty regions is determined through extracting features of regions in images by applying Morphological operations to detected rail images. In this work, all steps of the offered method is applied to the images of rail under different direction and lighting, and with maximum accuracy and minimum working time, the results are acquired. © 2015 IEEE.
Morfolojik Özellik Çikarimi Kullanan Görüntü Işleme Tabanli Ray Arizalarinin Tespiti
2015 23rd Signal Processing and Communications Applications Conference, SIU 2015 -- 16 May 2015 through 19 May 2015 -- Malatya -- 113052
Keywords: Edge Detection; Fault Detection; Hough Transform; Morphological Operations; Rail Systems